Why does mental health care not follow the structuring of primary care? - Antonio Moacir de Jesus Lima; Eli Iola Gurgel Andrade; Antonio Thomaz Gonzaga da Matta Machado; Alainer de Fátima dos Santos (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE: To verify if primary care teams with better structured primary health care (PHC) attributes could offer better mental health (MH) care. METHODS: Cross-sectional study based on data from the external evaluation of the second cycle of the Programa de Melhoria do Acesso e da Qualidade da Atenção Básica (PMAQ-AB - Access and Quality Improvement of Primary Care Program), involving 31,587 primary care teams, between 2013 and 2014. Two typologies were built: quality of mental health care (dependent variable) and PHC structuring according to essential attributes (independent variable). We identified some contents for the construction of the mental health typology (module II of the PMAQ) and performed sums of questions for the categorization of indices. The Delphi technique rendered consensus in four rounds endorsed by experts, following the attributes of PHC structure. Multinomial logistic regression analyses verified the association between the typologies and identified which attribute most contributed to the quality of mental health care. RESULTS: We found out that 29.2% of the teams are at low levels of quality in assistance to MH, while 7.5% of the teams have a low level of structuring the PHC according to essential attributes. Regional differences are maintained, both for the structuring of the PHC and for the quality of mental health care. There was a greater chance of providing care in MH with better quality when the PHC is better structured at a high level (OR = 14.74) and at a medium level (OR = 2.193). A high level of completeness is associated with a high level of Quality of Care in MH (OR = 3.21). CONCLUSION: results indicate a predominance of low levels of quality in mental health care, out of step with the process of PHC structuring and its essential attributes.